2019
DOI: 10.1007/s11192-019-03150-8
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and impact of research in different disciplines with international funding (from the EU and other foreign sources)

Abstract: The advancement of scientific research requires an adequate investment, which calls for promoting fair political decisions about the allocation of limited resources. In this context, funders need to be properly informed to assess the results of research lines or programmes. The WoS databases can help in making decisions, since they include the funding acknowledgements of documents along with additional useful data. The purpose of this paper is to analyse, in four different disciplines, the possible relation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
1
7
0
2
Order By: Relevance
“…On the other hand, in the general distribution of documents, it can be seen how the combination between FA and collaboration benefits citation, as it was already detected in previous works, especially for international funds (e.g. Álvarez-Bornstein et al 2019, Morillo 2019. Moreover, in this study, it has been found that OA publication improves the citation possibilities of this interaction.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, in the general distribution of documents, it can be seen how the combination between FA and collaboration benefits citation, as it was already detected in previous works, especially for international funds (e.g. Álvarez-Bornstein et al 2019, Morillo 2019. Moreover, in this study, it has been found that OA publication improves the citation possibilities of this interaction.…”
Section: Discussionsupporting
confidence: 81%
“…Funding analysis seeks insights into how and where the most significant public financial resources in science are used. Most previous bibliometric studies derive funding information from publications (Morillo, 2019;Zhou & Tian, 2014).…”
Section: Funding Datamentioning
confidence: 99%
“…Changes in the social environment and the development of disciplines have led to changes in the contribution of research funding to research output, and more scholars have discussed the quantification and influence factors of input-output analysis. Morillo (2019) analyzed the relationship between international funding and scholarly collaboration and the impact of outputs across four different disciplines, finding that authors of internationally funded articles showed a greater tendency to collaborate and their research outputs had a higher impact. Monrouxe, Liu, Yau, and Babovič (2020) compared the evolutionary characteristics of Science Citation Index (SCI) and non-Science Citation Index (non-SCI) articles in the field of professional health care education from 2006 to 2017.…”
Section: Scientific Research Fundingmentioning
confidence: 99%